The contract observed - SCPS pamphlet, 1977 (London, 1977)
1977 1974-79 "The contract observed - SCPS pamphlet, 1977" [BW0098], 1977, Trades Union Congress This is a critical review of the Social Contract and government policies on pay, prices and public expenditure, published by the Society of Civil and Public Servants.